The ‘Friending’ rules: Social norms of connection and disconnection at midlife - Quinn, Kelly (AoIR Selected Papers of Internet Research, 2013)
‘Friending’ is most commonly understood to convey the idea that some relationship exists between individuals, yet the unnuanced and decontextualized nature of social media connections and their discursive association with friendship has obscured the meaning of this practice. This study explores the meaning of the practices of connection and disconnection on social network sites at midlife. Using data from interviews with social media users between the ages 45 and 65 years, this research demonstrates contrasts in the meaning of such practices from those reported in studies of younger adults, and suggests differences in how these technologies are used to support relational development and maintenance.